2014
DOI: 10.1007/s12035-014-8743-4
|View full text |Cite
|
Sign up to set email alerts
|

Pan-PPAR Modulation Effectively Protects APP/PS1 Mice from Amyloid Deposition and Cognitive Deficits

Abstract: Alzheimer’s disease (AD) is a neurodegenerative condition that leads to neuronal death and memory dysfunction. In the past, specific peroxisome proliferator-activated receptor (PPAR)γ-agonists, such as pioglitazone, have been tested with limited success to improve AD pathology. Here, we investigated the therapeutic efficacy of GFT1803, a novel potent PPAR agonist that activates all the three PPAR isoforms (α/δ/γ) in the APP/PS1 mouse model in comparison to the selective PPARγ-agonist pioglitazone. Both compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…In view of the essential role of APH-1 in Ab production, our data further revealed that MgT treatment disrupted the binding between APH-1a/-1b and PS1, leading to the reduction of Ab in a PPARg-dependent manner. Consistent with our observations, Kummer et al (28) recently reported that oral treatment of APP/PS1 mice with a novel PPARa/b/g agonist, GFT1803, decreases Ab levels and the area affected by APs. More specifically, the PPARg agonist treatment was shown to improve cognitive decline in Figure 9.…”
Section: Discussionsupporting
confidence: 93%
“…In view of the essential role of APH-1 in Ab production, our data further revealed that MgT treatment disrupted the binding between APH-1a/-1b and PS1, leading to the reduction of Ab in a PPARg-dependent manner. Consistent with our observations, Kummer et al (28) recently reported that oral treatment of APP/PS1 mice with a novel PPARa/b/g agonist, GFT1803, decreases Ab levels and the area affected by APs. More specifically, the PPARg agonist treatment was shown to improve cognitive decline in Figure 9.…”
Section: Discussionsupporting
confidence: 93%
“…4). Some other data of Kummer et al [52] have detected that the new PPAR agonist activates all PPARs receptors (GFT1803) decreases significantly Aβ plaques/Aβ level and microglia activation in AD mice (APP/PS1). The data suggested the role of these receptors in Aβ degradation or clearance by i.e.…”
Section: The Role Ppar-α In App/aβ Metabolismmentioning
confidence: 90%
“…The ApoE ε4 allele frequency in IR patients is significantly higher than controls, with IR index and ApoE ε4 gene positively correlated, suggesting that IR is related to MCI and ApoE ε4, and that IR and ApoE ε4 have clinical application in predicting MCI occurrence and transformation into AD [106].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 98%